Polychaete species (Annelida) described from the Philippine and China Seas - Salazar-Vallejo, Sergio I.; Carrera-Parra, Luis F.; Muir, Alexander I.; de León-González, Jesús Angel; Piotrowski, Christina; Sato, Masanori (Zootaxa, 2014)
The South China and Philippine Seas are among the most diverse regions in the Western Pacific. Although there are several local polychaete checklists available, there is none comprising the whole of this region. Presented herein is a comprehensive list of the original names of all polychaete species described from the region. The list contains 1037 species, 345 genera and 60 families; the type locality, type depository, and information regarding synonymy are presented for each species.